The Practice of Assigning Patrons for Units of Local and Regional Government in the Podkarpackie Province - Szczygielski Krzysztof (Studies in Logic, Grammar and Rhetoric)
The issue of assigning a patron for a commune/municipality, dis-trict, or province is quite an important matter in local government activity, as indicated by the increased activity of local authorities in this field continuously since the Podkarpackie Province was established in January 1999. Local govern-ment bodies, when taking steps to assign a patron, usually decide to cooperate with the Catholic Church in these matters. The procedure for assigning a patron involves, in addition to local government bodies or church authorities, many dif-ferent types of entities, which clearly shows that the issue of choosing a patron for a unit of local government is seen as an important element in building social ties between the residents of a commune/municipality, district, or province. The coats of arms of numerous units of local and government in the Podkarpackie Province feature the figure of the patron and local authorities pay due attention to the principles of local government heraldry.